2010
DOI: 10.1359/jbmr.091004
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and fractures in postmenopausal women

Abstract: Low body mass index (BMI) is a recognized risk factor for fragility fracture, whereas obesity is widely believed to be protective. As part of a clinical audit of guidance from the National Institute of Health and Clinical Excellence (NICE), we have documented the prevalence of obesity and morbid obesity in postmenopausal women younger than 75 years of age presenting to our Fracture Liaison Service (FLS). Between January 2006 and December 2007, 1005 postmenopausal women aged less than 75 years with a low-trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
2
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(209 citation statements)
references
References 40 publications
12
175
2
20
Order By: Relevance
“…Obesity is often found to be a protective factor against hip fracture; (28,29) however, excess subcutaneous fat with less lean mass may alter the gait, thus predisposing individuals to falls. Indeed, obesity modifies the mechanical impact at the hip, which may consequently be transmitted to the diaphysis, (30) where the adipose tissue may have less shock-absorbing effect than at the hip. We also found that higher age is protective against ST/FS fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is often found to be a protective factor against hip fracture; (28,29) however, excess subcutaneous fat with less lean mass may alter the gait, thus predisposing individuals to falls. Indeed, obesity modifies the mechanical impact at the hip, which may consequently be transmitted to the diaphysis, (30) where the adipose tissue may have less shock-absorbing effect than at the hip. We also found that higher age is protective against ST/FS fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the mean BMI for postmenopausal women presenting with a fracture in a UK study was 27.4 kg/m 2 , and 28% of cases were obese (BMI 30 kg/m 2 ). (30) In the Million Women Study in the UK, almost one-half of all postmenopausal hip fractures occurred in women who were overweight or obese: 40% were overweight (BMI 25-29.9 kg/m 2 ) and 9% were obese (BMI 30 kg/m 2 ). (17) In a large longitudinal study of older U.S. men, 68% of all incident clinical fractures and 62% of incident hip fractures occurred in those who were overweight or obese; 19% of all clinical fractures and 13% of hip fractures occurred in obese men.…”
Section: Predominance Of Overweight and Obesity Among Fracture Casesmentioning
confidence: 99%
“…(20) There are strong reasons to expect a pathophysiologic linkage between fat and bone tissue. Osteoblasts and adipocytes in bone marrow originate from the same mesenchymal stem cells, (21) normal aging is associated with a high incidence of both osteoporosis and bone marrow adiposity, (22,23) and both bone remodeling and adiposity are regulated by the hypothalamus and sympathetic nervous system.…”
mentioning
confidence: 99%